1989
DOI: 10.1038/clpt.1989.67
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of meso-2,3-dimercaptosuccinic acid in human subjects

Abstract: The urinary excretion of meso-2,3-dimercaptosuccinic acid (DMSA), which is an effective chelating agent for lead, was determined after the oral administration of 10 mg DMSA/kg to six normal young men. The DMSA that was absorbed was extensively biotransformed. After 14 hours only 2.53% of the administered DMSA was excreted in the urine as unaltered DMSA and 18.1% as altered forms. The unaltered DMSA was 12% of the total DMSA found in the urine. The altered form(s) of DMSA was 88% of the total urinary DMSA. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 0 publications
0
39
0
Order By: Relevance
“…Observed DMSA concentrations in plasma were available only in the Maiorino et al [10] study (upper panel). Observed urine data were reported only in the Aposhian et al [17] and Maiorino et al [10] studies (lower panel). As the predicted values were calculated for the same DMSA dose (oral administration of 10 mg/kg DMSA) and standard weight, both predicted curves of the upper panel are similar.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Observed DMSA concentrations in plasma were available only in the Maiorino et al [10] study (upper panel). Observed urine data were reported only in the Aposhian et al [17] and Maiorino et al [10] studies (lower panel). As the predicted values were calculated for the same DMSA dose (oral administration of 10 mg/kg DMSA) and standard weight, both predicted curves of the upper panel are similar.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 shows the calculated and measured plasma and urine DMSA concentrations in three studies. [10,13,17] In the Dart et al [13] study, observed blood DMSA concentrations were provided and had to be converted into plasma DMSA concentrations for comparison purpose (upper panel). Observed DMSA concentrations in plasma were available only in the Maiorino et al [10] study (upper panel).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations